Depressive disorders in athletes - Beabl, S. E. (Clinics in Sports Medicine, 2024)
Depressive disorders in athletes are thought to be at least as common as the general population. However, athletes have a unique set of risk factors that can affect the likelihood of developing depression. Screening tools have been developed specifically for athletes such as the Sport Mental Health Assessment Tool (SMHAT). The management of the depressed athlete should involve an individualized approach, with methods such as counseling, interpersonal therapy, or cognitive behavioral therapy being used. Some may require antidepressant medication. Depressive disorders are also linked to sucidality in athletes, and the team physician and sporting organisation should have a crisis management plan in place for mental health emergencies. Tackling the stigma that remains in sport is a key part to improving mental wellbeing for all athletes.